The Role of Permissive and Induced Hypotension in Current Neuroanesthesia Practice - Soghomonyan, Suren; Stoicea, Nicoleta; Sandhu, Gurneet S.; Pasternak, Jeffrey J.; Bergese, Sergio D. (Frontiers in Surgery, 2017)
Background: Induced hypotension (IH) had been used for decades in neurosurgery to reduce the risk for intraoperative blood loss and decrease blood replacement. More recently, this method fell out of favor because of concerns for cerebral and other end-organ ischemia and worse treatment outcomes. Other contributing factors to the decline in its popularity include improvements in microsurgical technique, widespread use of endovascular procedures, and advances in blood conservation and transfusion protocols. Permissive hypotension (PH) is still being used occasionally in neurosurgery; however its role in current anesthesia practice remains unclear. Our objective was to describe contemporary utilization of IH and PH (collectively called PH) in clinical practice among members of the Society for Neuroscience in Anesthesiology and Critical Care (SNACC). Methods: A questionnaire was developed and distributed among SNACC members that addressed practice patterns related to the use of PH. The responses were analyzed based on the number of individuals who responded to each specific question. Results: Of 72 respondents, 67.6% reported over 10 years of clinical experience, while 15.5% reported 5-10 years of post-training experience. The respondents admitted to providing anesthesia for 300 (median) neurosurgical cases per year. PH was applied most commonly during open interventions on cerebral aneurysms (50.8%) and arteriovenous malformations (46%). Seventy-three percent of respondents were not aware of any complications in their practice attributable to PH. Conclusions: PH is still being used in neuroanesthesia practice by some providers. Further research is justified to clarify the risks and benefits of PH in modern neuroanesthesia practice.